Made in China : what western managers can learn from trailblazing Chinese entrepreneurs - Sull, Donald N.; Yong,Wang (Boston, 2005)
Introduces managers to some of China's entrepreneurs, reveals the success strategies that have enabled them to compete so effectively, and codifies these strategies into a set of principles for managing in China or any turbulent environment.
Keywords: Business entrepreneurs- China; Entrepreneurship- China